Military pedagogy as a component of personnel management in the Defense Forces of Ukraine: ontological dimension - Gurkovskyi, Volodymyr; Semenenko, Lilia; Romanenko, Yevhen; Dobrovolskyi, Yuzef; Polishchuk, Oleksandr; Tkach, Ivan (Social Development and Security, 2024)
Purpose: To conduct an ontological analysis of military pedagogy and to highlight its role in the personnel management of the Defense Forces of Ukraine in the conditions of modern military threats. The study will examine the essence of military pedagogy, its structural components, as well as its importance for ensuring effective training of military personnel. Method: Methods of analysis, comparison, generalization and interpretation of research results in the field of military pedagogy were used, taking into account Ukrainian and international experience. Findings: The study is aimed at improving the system of training military personnel, in particular, at developing recommendations for reforming military education and personnel management. Value of the study: The article highlights the relevance of implementing innovative approaches in military pedagogy, which will increase the effectiveness of training military specialists to perform tasks in the face of modern challenges. Based on the results of the study, it was concluded that the development of military pedagogy is an important element of Ukraine’s integration with the North Atlantic Alliance. Future research: Areas of future research include analyzing the impact of innovative technologies on the process of training military personnel, developing methods for psychological rehabilitation and adaptation of military personnel after participation in combat operations.